The Evolution of Yunnan’s Tile Cats: From Sacred Rooftops as a Bridge to Cultural and Creative Products - Nanxin , Dai; Chartniyom, Pensiri (Journal of Roi Kaensarn Academi, 2024)
As a unique ethnic cultural element, the Yunnan Tile Cats holds an important position in the local society of Yunnan. This study aims to explore the transformation of Yunnan Tile Cats from a sacred roof decoration to a cultural and creative product, analyze its cultural connotation and symbolic meaning, and discuss the development and commercialization process of Tile Cats as a creative product. The research adopts methods such as literature research, field investigation, and case analysis, and analyzes the evolutionary trajectory of Yunnan Tile Cats and its new vitality in modern society from the perspectives of cultural transformation theory and creative product development theory. The study finds that Yunnan Tile Cats has experienced a transformation from a religious symbol to a cultural symbol and then to a creative product, reflecting the survival and development.